2016
DOI: 10.1177/1088868315601613
|View full text |Cite
|
Sign up to set email alerts
|

Homosexuality and Pro-Gay Ideology as Pathogens? Implications of a Disease-Spread Lay Model for Understanding Anti-Gay Behaviors

Abstract: Negative behaviors targeting gay men and lesbians range from violent physical assault to casting a vote against gay marriage, with very different implications for those targeted. Existing accounts of such actions, however, are unable to differentially predict specific anti-gay behaviors, leaving a large theoretical hole in the literature and hindering the design of effective interventions. We propose (a) that many sexually prejudiced laypersons conceptualize homosexuality and pro-gay ideology as "contaminants"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 172 publications
(259 reference statements)
1
15
0
Order By: Relevance
“…Dissenters who deviate from traditional sexual norms are especially likely to be stigmatized during the outbreaks of infectious disease because they are construed metaphorically COVID-19, NATIONAL CONTINUITY, SEXUAL PREJUDICE as an contaminant (Filip-Crawford & Neuberg, 2016) and prejudice towards them is expressed as disgust (Cottrell & Neuberg, 2005). Disgust is an affective reaction to bodily contamination and a moral emotion characterizing responses to violation of values of purity (Haidt et al, 1997).…”
Section: Sexual Dissenters and The Metaphor Of Contaminationmentioning
confidence: 99%
“…Dissenters who deviate from traditional sexual norms are especially likely to be stigmatized during the outbreaks of infectious disease because they are construed metaphorically COVID-19, NATIONAL CONTINUITY, SEXUAL PREJUDICE as an contaminant (Filip-Crawford & Neuberg, 2016) and prejudice towards them is expressed as disgust (Cottrell & Neuberg, 2005). Disgust is an affective reaction to bodily contamination and a moral emotion characterizing responses to violation of values of purity (Haidt et al, 1997).…”
Section: Sexual Dissenters and The Metaphor Of Contaminationmentioning
confidence: 99%
“…For instance, research has indicated that heterosexual and homosexual groups differ in neurodevelopment (e.g. Santtila et al, 2008), social pressure (Filip-Crawford & Neuberg, 2016), and mating market (Black, Gates, Sanders, & Taylor, 2000). Consequently, homosexual people might exhibit different ideal partner preference patterns.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In this context, one of the highly relevant domains concerns social attitudes, as they often have disease-related origins (Faulkner et al, 2004). Here, we focus on homosexual individuals, both men and women, who have been frequently framed as "unclean, " and associated with germs and diseases (such as AIDS) (Crandall et al, 1997;Herek, 2002;Greene and Banerjee, 2006;Golec de Zavala et al, 2014;Pachankis et al, 2015;Filip-Crawford and Neuberg, 2016).…”
Section: Introductionmentioning
confidence: 99%